The effect of halal supply chain management on halal integrity assurance for the food industry in Malaysia. Issue 9 (17th July 2020) - Mohamed, Yusaini Hisham; Abdul Rahim, Abdul Rahman; Ma'aram, Azanizawati
Abstract : Purpose: The purpose of this study is to outline the results of the empirical testing in the field of halal food supply chain and halal integrity assurance (HIA), as well as to provide a research framework of their relationships. Design/methodology/approach: This study is based on the exploratory research paper using quantitative data collection to empirically experimented with concepts and provide practical solutions for halal industry players to optimize their halal food supply chain integrity assurance. Findings: The findings show the halal supply chain of the food and beverage industry has a significant effect on HIA. The results also suggest the halal industry with a high focus on supply chain business processes and supply chain network structure are expected to have better HIA. Research limitations/implications: As this study only focuses on the halal industry in Malaysia specifically on food and beverages, its findings cannot be generalized to other categories. Issues of applicability of this study to other countries also need to be considered. Practical implications: This study addresses the assurance of halal integrity is a crucial element in managing a halal food supply chain in the halal industry. It has empirically identified the important elements to strengthen halal food supply chain integrity assurance in the halal industry. Social implications: It is important to manage knowledge, commitment and trust in any halal organization as a catalyst for HIA. This study presents a better understanding of the halal concept application in society. Originality/value: There is a lack of empirical study on halal food supply chain integrity assurance even though the issue of HIA is widely discussed in the halal industry. Thus, this study has used an industry survey to empirically experimented with concepts and provide practical contributions to enhance halal food supply chain integrity assurance.